MAPK Regulation of IL-4/IL-13 Receptors Contributes to the Synergistic Increase in CCL11/Eotaxin-1 in Response to TGF- beta 1 and IL-13 in Human Airway Fibroblasts - Zhou, Xiuxia; Hu, Haizhen; Balzar, Silvana; Trudeau, John B; Wenzel, Sally E (The Journal of immunology (1950), 2012)
CCL11/eotaxin-1 is a potent eosinophilic CC chemokine expressed by primary human fibroblasts. The combination of TGF- beta 1 and IL-13 synergistically increases CCL11 expression, but the mechanisms behind the synergy are unclear. To address this, human airway fibroblast cultures from normal and asthmatic subjects were exposed to IL-13 alone or TGF- beta 1 plus IL-13. Transcriptional (nuclear run-on) and posttranscriptional (mRNA stability) assays confirmed that transcriptional regulation is critical for synergistic expression of CCL11. TGF- beta 1 plus IL-13 synergistically increased STAT-6 phosphorylation, nuclear translocation, and binding to the CCL11 promoter as compared with IL-13 alone. STAT-6 small interfering RNA significantly knocked down both STAT-6 mRNA expression and phosphorylation and inhibited CCL11 mRNA and protein expression. Regulation of the IL-4R alpha complex by TGF- beta 1 augmented IL-13 signaling by dampening IL-13R alpha 2 expression, overcoming IL-13's autoregulation of its pathway and enhancing the expression of CCL11. Our data suggest that TGF- beta 1 induced activation of the MEK/ERK pathway reduces IL-13R alpha 2 expression induced by IL-13. Thus, TGF- beta 1, a pleiotropic cytokine upregulated in asthmatic airways, can augment eosinophilic inflammation by interfering with IL-13's negative feedback autoregulatory loop under MEK/ERK-dependent conditions.